Comparative Study on Sequence–Structure–Function Relationship of the Human Short-chain Dehydrogenases/Reductases Protein Family. (January 2014) - Tang, Nu Thi Ngoc; Le, Ly
Human short-chain dehydrogenases/reductases (SDRs) protein family has been the subject of recent studies for its critical role in human metabolism. Studies also found that single nucleotide polymorphisms of the SDR protein family were responsible for a variety of genetic diseases, including type II diabetes. This study reports the effect of sequence variation on the structural and functional integrities of human SDR protein family using phylogenetics and correlated mutation analysis tools. Our results indicated that (i) tyrosine, serine, and lysine are signature protein residues that have direct contribution to the structural and functional stabilities of the SDR protein family, (ii) subgroups of SDR protein family have their own signature protein combination that represent their unique functionality, and (iii) mutations of the human SDR protein family showed high correlation in terms of evolutionary history. In combination, the results inferred that over evolutionary history, the SDR protein family was able to diverge itself in order to adapt with the changes in human nutritional demands. Our study reveals understanding of structural and functional scaffolds of specific SDR subgroups that may facilitate the design of specific inhibitor.